The challenges associated with the teaching of English composition writing skills in Khami District in Bulawayo Metropolitan Province in Zimbabwe - Gumpo, Nonhlanhla (Midlands State University, 2018)
The study sought to explore the challenges associated with teaching of English composition writing in Khami district. The study adopted a qualitative research paradigm .The study adopted a survey design in which questionnaires were distributed to teachers and interviewees were administered to teachers in charge , deputy heads and heads of primary schools in Khami district .A total of 45 questionnaires were distributed to the teachers in three primary schools of Khami district .The researcher also conducted interviews with heads of schools, deputy heads of schools and teachers in charge from three primary schools in Khami district. Both secondary and primary data sources were used to gather data. The research findings revealed that the major method which is used by teachers to teach English composition writing in Khami district is product approach .The study revealed that the major challenges associated with teaching English composition writing were grammatical difficulties faced by the learners. The study also indicated that the main measures used to effective teach English composition writing are provision of feedback on learners written assessments and provision of adequate resources for teaching English composition writing. The study recommended that the parents should support their children in learning English composition writing, the schools should avail enough resources for the teaching of English composition writing and the learners should be motivated to learn English composition writing through provision of prizes to the best performers. Further study should be conducted on the impact of the methods used by teachers in teaching English language grammar on composition writing.